Volatile Oil Composition of Ballota nigra L. ssp. anatolica P. H. Davis, Growing in Mazandaran Province - Z Kazemizadeh; T Amini (Institue of Medicinal Plants, ACECR, 2009)
Background: The genus Ballota (Lamiaceae) is comprised of about 90 species all over the world. Remarkably, three species of this genus are growing in Iran, that is used in traditional medicine [1]. Objective: Investigation on the essential oil composition of Ballota nigra ssp. anatolica. Methods: The aerial parts of B. nigra ssp. anatolica were collected during the flowering stage from Shahnajar village, Kojur, Mazandaran Province, in July 2007. Hydrodistillation was performed using a Clevenger-type apparatus for 3 hours to yield 0.7% (w/w) of yellowish oil. Essential oil was analyzed with GC and GC/MS techniques. The constituents of the essential oil were identified by comparison of their mass spectra and retention indices (RI) with those given in the literature and authentic samples. Results: Twelve components were determined in the essential oil of B. nigra spp. anatolica, representing 91.8% of the oil. Conclusion: Germacrene D (18.1%), Nerolidol epoxyacetate (15.4%), Sclareoloxide (12.1%), Linalyl acetate (11.5%), β - Caryophyllene (10.5%), were found to be the major constituents. The oil of B. nigra spp. anatolica consists of oxygenated monoterpens (18.1%) and sesquiterpens (73.7%).